2018
DOI: 10.1007/s12020-018-1696-z
|View full text |Cite|
|
Sign up to set email alerts
|

Adrenocortical incidentalomas and bone: from molecular insights to clinical perspectives

Abstract: Adrenal incidentalomas constitute a common clinical problem with an overall prevalence of around 2-3%, but are more common with advancing age being present in 10% of those aged 70 years. The majority of these lesions are benign adrenocortical adenomas (80%), characterized in 10-40% of the cases by autonomous cortisol hypersecretion, and in 1-10% by aldosterone hypersecretion. Several observational studies have shown that autonomous cortisol and aldosterone hypersecretion are more prevalent than expected in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 90 publications
1
22
0
Order By: Relevance
“…However, ECS is the most frequent endocrine paraneoplastic syndrome reported in NET [47]. It has well demonstrated that cortisol excess has a negative impact on bone health [48][49][50]. Osteoporosis induced by glucocorticoid excess is due mainly to a direct effect on osteoblasts, osteocytes, and osteoclasts, which express glucocorticoid receptors (GR; Figure 3) [49].…”
Section: Hormone Hypersecretionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ECS is the most frequent endocrine paraneoplastic syndrome reported in NET [47]. It has well demonstrated that cortisol excess has a negative impact on bone health [48][49][50]. Osteoporosis induced by glucocorticoid excess is due mainly to a direct effect on osteoblasts, osteocytes, and osteoclasts, which express glucocorticoid receptors (GR; Figure 3) [49].…”
Section: Hormone Hypersecretionmentioning
confidence: 99%
“…It has well demonstrated that cortisol excess has a negative impact on bone health [48][49][50]. Osteoporosis induced by glucocorticoid excess is due mainly to a direct effect on osteoblasts, osteocytes, and osteoclasts, which express glucocorticoid receptors (GR; Figure 3) [49]. In osteoblasts, cortisol excess induces a reduction of bone formation mediated by an upregulation of peroxisome proliferator-activated receptor (PPAR)-γ and an inhibition of the wnt pathway, which promotes, in turn, osteoblast apoptosis and differentiation of mesenchymal progenitors into adipocytes.…”
Section: Hormone Hypersecretionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excess of pure adrenal androgens is extremely rare in cases without other secretions and these cases are not usually asymptomatically at presentation so they can barely fit to the diagnosis of adrenal incidentaloma (7,8). The cortisol excess (even subclinical) is more frequent in subjects with bone loss or vertebral fractures (4,9).…”
Section: General Data Adrenal Incidentalomamentioning
confidence: 99%
“…The finding has an age-dependent pattern (2,3). The diagnosis actually includes two aspects: one is the radiological or imaging detection through any of the mentioned procedures, and the other aspect is related to the clinical and endocrine assessment that finally decides that the incidental tumour is a "true" incidentaloma meaning that overall there is a negative secretor profile and the route to its detection was accidental (4,5). However, a possible or a probable autonomous cortisol production is included and thus some long term complications might be expected, ignored or considered "idiopathic" or just "age-related" as seen in subjects diagnosed with high blood pressure, hyperlipemia and osteoporosis especially in menopausal women (1,5,6).…”
Section: Introductionmentioning
confidence: 99%